REDUCED VOLTAGE STRESS EXTENDABLE SEVENTEEN-LEVEL MULTILEVEL INVERTER USING SINGLE VOLTAGE SOURCE - Routray A.; Singh A.; Shiluveru K.; Kumar P.; Singh R.K.; Mahanty R. (My University, 2025)
In this paper a switched capacitor based multilevel inverter (SC-MLI) is presented which can generate 17 voltage levels. It uses a dc voltage source, while restraining the peak inverse voltage (PIV) of all the circuit components (switches and diodes) within the input dc source voltage. This reduction in the PIV of switches and diodes ensures the use of lower rated power devices in the proposed SC-MLI and the total standing voltage (TSV) of the proposed scheme is reduced. The capacitors are inherently self-balanced using series-parallel combinations dc source and capacitors. It does not require any voltage balancing mechanism. proposed SC-MLI is compared with other reported SC-MLIs in terms of circuit elements PIV and TSV. The performance of the proposed inverter is verified experimentation using a through 500 W laboratory prototype. © 2020 IET Conference Proceedings. All rights reserved.